STUDI PEMBUATAN TAHU DARI BIJI NANGKA (Artocarpus heterophyllus Lamk.) DENGAN PENAMBAHAN CaSO4 DAN LAMA PENGGUMPALAN - Budi Suarti; Dani Budi Mahyono; M. Said Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The objectives study was to investigate the effect of  CaSO4  consentrations and clotting time on quality of  jackfruit seed tofu. This study used a completely randomized  factorial design with  two replications. The first factor is CaSO4 consentration (C), which consists of 4 levels are: C1 = 1%, C2 = 2%, C3 = 3% and C4 = 4%. The second factors is clotting time (L) consisting of 4 levels, namely: L1 = 30 minutes,  L2 = 60 minutes, L3 = 90 minutes and L4 = 120 minutes. Parameters that observed: protein content, sucrose content, organoleptic color, flavor and texture. CaSO4 consentration and clotting time influenced the protein and sugar content, organoleptic color, flavor and texture. Keywords: tofu, jackfruit seeds, calcium sulfate, clotting.